Electronic petitions in France on the material of Change.org, a non-governmental e-petition platform - K. V. Bannikov; N. K. Radina; O. A. Smirnova; D. V. Shavarova (Цифровая социология, 2022)
The article presents the results of an empirical study on electronic petitions posted on the Change.org French-speaking segment, geographically linked to France. The relevance of the topic is due to the intervention of modern information and communication technologies in political reality and the need for scientific reflection of the consequences of digital changes in political processes. The authors of the article analyse the regional particularities of the online petition activity by the inhabitants of France on the material of 15 887 electronic petitions (January 2015 – October 2017), 570 of which are petitions with the status of “victory” (4 %). The authors note that the European territories of France form three main groups of online petition activity (with low, medium and high petition activity). Residents of France most often relate to social problems (social security, health care and education) in electronic petitions. In addition, Change.org is actively registering electronic petitions on issues related to crime and terrorism, discrimination, the environment, the economy and animal welfare. Electronic petitions about problems of culture, sports and problems of confessional relations are recorded relatively rarely. The greatest response from the recipients of the petition is caused by problems in the social sphere, education and health. The French society, through the prism of activity on the non-governmental Internet resource Change.org, appears as a modern society with post-industrial values, preoccupied with security issues, in an active and relatively productive dialogue with its political and business elite.